A Project Report on Cloud Computing for Agent based Urban Transporation System - BHARAT SURANA, DURGESH, NABIN PRADHAN and SURAJEET GOGOL (2011)
INTERNAL GUIDE: MUTHAIAH U, MVJCE
Keywords: Urban Transporation System